Epidemiologic Review of Veterans Health Administration Patients with Isolation of Nontuberculous Mycobacteria after Cardiopulmonary Bypass Procedures. (11th July 2017) - Oda, Gina; Ryono, Russell; Lucero-Obusan, Cynthia; Schirmer, Patricia; Shanawani, Hasan; Jacobs, Katrina; Holodniy, Mark
Abstract : We evaluated the isolation of postoperative nontuberculous mycobacteria (NTM) associated with heater-cooler devices (HCDs) used during cardiopulmonary bypass (CPB) surgery in the Veterans Health Administration from January 1, 2010, to December 31, 2016. In more than 38, 000 CPB procedures, NTM was isolated in 111 patients; 1 Mycobacterium chimaera mediastinitis case and 1 respiratory isolate were found. Infect Control Hosp Epidemiol 2017;38:1103–1106